2021
DOI: 10.1097/nnd.0000000000000764
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Simulation to Reinforce Nursing Staff Resuscitation Responses

Abstract: In-hospital cardiac arrests have high mortality rates, increased by delayed resuscitation. Using a single group pre–post interventional design to implement virtual cardiac arrest simulations for medical-surgical units, the purpose of this project was to decrease resuscitation delays and improve self-confidence of the nursing staff. Both response times and confidence improved following virtual simulation. Conducting virtual simulation for resuscitation training may be a valuable alternative to in situ simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…There were included 15 studies (Table 1 ) published between 2013 and 2023 and conducted in Europe [ 18 , 19 , 27 29 ], in North America [ 20 , 24 , 25 , 31 ], in Africa [ 32 , 33 ], in Asia [ 26 , 30 ], and in Central America [ 23 ]; one study did not report the country [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were included 15 studies (Table 1 ) published between 2013 and 2023 and conducted in Europe [ 18 , 19 , 27 29 ], in North America [ 20 , 24 , 25 , 31 ], in Africa [ 32 , 33 ], in Asia [ 26 , 30 ], and in Central America [ 23 ]; one study did not report the country [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six were primarily aiming to investigate the efficacy of VR CPR training [ 18 , 23 , 25 , 29 , 31 , 33 ], four its feasibility [ 22 , 28 , 29 , 32 ], three its utility [ 19 , 24 , 30 ], and two its usability [ 20 , 26 ]. To reach these aims, six were RCTs [ 22 , 25 , 27 , 29 , 31 , 33 ], six were cross-sectional studies [ 19 , 20 , 24 , 26 , 28 , 30 ] , and three quasi experimental [ 18 , 23 , 32 ] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, SBEs included learning experiences with standardized patients or high-fidelity manikins. However, COVID-19 restrictions limited in-person instruction, making virtual simulation a viable alternative (Brzozowski et al, 2021). A systematic review conducted by Foronda et al (2020) found that most randomized controlled trials demonstrated an increase in knowledge and self-confidence after virtual simulation training.…”
Section: Available Knowledgementioning
confidence: 99%
“…A systematic review conducted by Foronda et al (2020) found that most randomized controlled trials demonstrated an increase in knowledge and self-confidence after virtual simulation training. Moreover, virtual simulations offer a low-cost alternative to in-person, high-fidelity simulation (Brzozowski et al, 2021). Despite the known effectiveness of in-class SBEs and virtual simulation in undergraduate curriculum, little evidence exists on the use of these strategies after graduation in NGRN residency programs.…”
Section: Available Knowledgementioning
confidence: 99%